PREVALENCE OF FREQUENCY OF PATIENTS UNDERGOING EXTRACTION FOR ORTHODONTIC TREATMENT - AN INSTITUTIONAL BASED RETROSPECTIVE STUDY - H., Firdus Fareen; Srirengalakshmi (International Journal of Psychosocial Rehabilitation, 2020)
Extraction of permanent teeth as a part of orthodontic treatment has been the topic of discussion for many years, including periods when it was widely used in treatment, including the present, during which other methods are used to avoid dental extractions. The aim of the study was to evaluate the frequency of patients undergoing extraction for orthodontic treatment at Private dental college. The clinical records of 987 patients undergoing orthodontic treatment were evaluated. The frequency of extractions was evaluated with regard to sex, gender and the different combinations of extractions was assesed. Chi-square test was used to determine correlations between variables, while the chi-square test for trends was used to assess the frequency of extractions. The most frequently extracted teeth were first premolars. There was a statistically significant differences seen in patients undergoing extraction for orthodontic treatment with regard to age. New features introduced into the orthodontic clinic and new esthetic concepts contributed to reducing the number of cases treated with dental extractions. However, dental extractions for orthodontic treatments are still well indicated in certain cases.